IRAK4 and TLR3 Sequence Variants may Alter Breast Cancer Risk among African-American Women - Yeyeodu, Susan T.; Kidd, La Cries R.; Oprea, Gabriela M.; Vancleave, Tiva T.; Shim, Joong-Youn; Kimbro, Kevin S. (Frontiers in Immunology, 2013)
Mounting evidence suggests that imbalances in immune regulation contribute to cell transformation. Women of African descent are an understudied group at high risk for developing aggressive breast cancer (BrCa). Therefore, we examined the role of 16 innate immune single nucleotide polymorphisms (SNPs) in relation to BrCa susceptibility among 174 African-American women in Atlanta, GA. SNPs were examined in germ-line DNA collected from 102 BrCa patients and 72 women with benign nodules using SNPstream methodology. Inheritance of the TLR3 rs10025405 GG genotype was associated with an 82% decrease in BrCa risk. In contrast, individuals who possessed at least one IRAK4 rs4251545 T allele had a 1.68-4.99-fold increase in the risk of developing BrCa relative to those with the referent genotype (OR = 4.99; 95% CI = 1.00, 25.00; p = 0.0605). However, the IRAK4 rs4251545 locus was only significant under the additive genetic model (p trend = 0.0406). In silico predictions suggest IRAK4 rs4251545 SNP falls within a transcription enhancer/silencer region of the gene and codes for an Ala428Thr amino acid change. This missense mutation introduces a potential phosphorylation site in the extreme carboxy terminus (XCT) of the IRAK-4 kinase domain. Preliminary molecular modeling predicts that this SNP stabilizes two alpha helices within the XCT on the surface of the IRAK-4 kinase domain and increases the size of the groove between them. Our in silico results, combined with previous reports noting the presence of IRAK-4 and XCT fragments in mouse and human serum, suggest the possibility that the XCT subdomain of IRAK-4 possesses biological function. These findings require further evaluation and validation in larger populations, additional molecular modeling as well as functional studies to explore the role of IRAK-4 and its XCT in cell transformation and innate immunity.